Documentary Letter of Credit: A Pivotal Case for the Inefficiency of the Law of Contract - Chmielewska, Malgorzata (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2005)
This study compares the methods used both in common law and civil law jurisdictions to deal with the basic problems relating to the documentary letter of credit. A unique commercial device was thus developed in international trade as a means of ensuring safe and swift payment for goods. Even though this distinct mechanism works efficiently in practice, the numerous attempts made to classify it legally have been unsuccessful.A comparative analysis of the legal conceptualizations traditionally used to explain the nature of credit reveals apparent shortcomings in contractual theories. Because the basis of the documentary credit appears to be an abstract promise to pay, this phenomenon seems to break through the conceptual framework of traditional contract law theory. This is due to the fact that the process of forming the credit does not fit into the ordinary offer-acceptance formula. Yet, the easiest solution—the credit as a "mercantile specialty" or a "sui generis contract"—avoids facing the true challenge of our era, which is re-thinking the concept of "contracts" under modern laws. Legal debates should be directed in a more functional direction in order to provide satisfactory theoretical grounds for providing solutions to obvious, but still unanswered questions such as why people ought to keep their promises and why only some of those promises are likely to be legally enforced. It seems that, in this regard, documentary credit would be a convenient "guinea pig" for most contemporary concepts relating to the law of contracts.